Lithium ion battery negative electrode material as well as preparation method and application thereof
Through the combination of electrolytic, sintering, and water heat reactions, the lithium -ion battery negative electrode material is prepared, the problem of insufficient the performance of traditional lithium battery negative materials is solved, and high -capacity, stability, and magnification performance are achieved. It is suitable for high -power energy storage applications.
Patent Information
- Application Number
- CN202411432771.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-24
Smart Images

Figure CN119352045A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of preparation of negative electrode materials for lithium ion batteries, and in particular to a negative electrode material for lithium ion batteries and a preparation method and application thereof. Background Art
[0002] As energy shortages and environmental pollution become increasingly serious, the development of sustainable new energy sources has become the focus of current attention and research, and the development of large-scale energy storage technology has also received increasing attention. Lithium-ion secondary batteries have been widely promoted and applied due to their advantages such as high operating voltage, high energy density, long cycle life and low self-discharge rate.
[0003] However, conventional lithium-ion batteries cannot meet the rapidly growing requirements for high-power energy storage due to their poor safety and reduced cycle performance. Exploring safe, high-performance lithium-ion battery anode materials has always been a hot topic of research. Niobium-based materials have been shown to be promising anodes for high-speed energy storage applications due to their fast electrochemical ion insertion and extraction kinetics. However, so far, research on NaNbO 3 Comparative studies on the effects of morphology on the performance of lithium-ion batteries (LIBs) are still lacking.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first object of the present invention is to provide a method for preparing a negative electrode material for a lithium ion battery. The method adopts a combination of electrolysis, sintering and hydrothermal reaction to achieve the advantages of high specific capacity, high cycle stability and significant intercalation pseudocapacitive behavior of the prepared lithium ion battery negative electrode material.
[0006] The second purpose of the present invention is to provide a lithium-ion battery negative electrode material prepared by the above-mentioned preparation method, which solves the technical problems of poor capacity, poor preparation difficulty and low rate of lithium battery negative electrode materials in the prior art, and achieves the technical effects of good ion mobility, good cycle stability and cost reduction of lithium battery negative electrode materials.
[0007] The third object of the present invention is to provide further application of the above-mentioned lithium ion battery negative electrode material, which has been proven to have excellent application effects in device driving.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] The present invention provides a method for preparing a negative electrode material for a lithium ion battery, comprising the following steps:
[0010] The niobium wire and the carbon rod are used as the two ends of the electrode, an inorganic solution is used as the electrolyte, the AC voltage is controlled between 6-10V, and electrolysis is filtered to obtain a precipitate, and the precipitate is subjected to high-temperature sintering and hydrothermal reaction to obtain a negative electrode material for a lithium-ion battery.
[0011] Preferably, as a further feasible solution, the inorganic solution includes at least one of sodium chloride, sodium hydroxide, hydrochloric acid and lithium chloride, preferably hydrochloric acid.
[0012] Preferably, the concentration of the inorganic solution is 0.5-10 mol / L, and can also be 1 mol / L, 2 mol / L, 3 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, and the like.
[0013] The method for preparing a negative electrode material for a lithium ion battery provided by the present invention has a process route of first preparing the material by an alternating current method. The reason for first adopting this method is that it can effectively shorten the crystallization induction period, accelerate the crystallization speed, thereby improving the product yield and reducing the production cost. This method can narrow the particle size distribution range of the product and reduce the content of impurities contained in the product, thereby obtaining a product with uniform particles and high purity.
[0014] Then, after the alternating current treatment, the prepared material needs to be sintered at high temperature. The purpose of this is to transform the material from an amorphous structure into a fixed structure, while removing excess carbon impurities. Through hydrothermal reaction, the interlayer spacing is further increased to improve the capacity, thereby solving the technical problems of poor capacity, poor cycle stability, and low rate of lithium battery negative electrode materials in the prior art.
[0015] Finally, hydrothermal treatment is required after high-temperature sintering in order to further improve the performance of the prepared battery materials. Practice has shown that electrolysis alone is not enough and that electrolysis, high-temperature calcination and hydrothermal reaction need to be coordinated to achieve good results.
[0016] In summary, the preparation method provided by the present invention is a new process route specifically explored for sodium niobate, a battery material, with fewer operating steps, simple process, high success rate, and is suitable for large-scale promotion and production.
[0017] In particular, the types and concentrations of inorganic solutions used in the electrolysis process, as well as the voltage control parameters are obtained through a lot of practice, and therefore need to be controlled within an appropriate operating range to achieve good results.
[0018] Preferably, as a further feasible solution, the high temperature sintering temperature is 400° C.-700° C., and the high temperature sintering time is 6-15 hours.
[0019] Preferably, the high temperature sintering temperature is 450° C.-650° C., and the high temperature sintering time is 8 h-14 h.
[0020] Preferably, the high temperature sintering temperature is 450° C.-600° C., and the high temperature sintering time is 9 h-13 h.
[0021] Preferably, as a further feasible solution, the temperature of the hydrothermal reaction is 100-200° C., and the time of the hydrothermal reaction is 3-12 h.
[0022] Preferably, the temperature of the hydrothermal reaction is 150-200° C., and the time of the hydrothermal reaction is 4-10 h.
[0023] Preferably, as a further feasible scheme, the acid used in the hydrothermal reaction includes at least one of acetic acid, succinic acid, oxalic acid, malonic acid, hydrochloric acid, formic acid, propionic acid and oxalic acid, preferably hydrochloric acid.
[0024] Generally, the amount of acid added is slightly greater than that calculated based on the mass of the material obtained by sintering.
[0025] Preferably, as a further implementable scheme, the electrolysis time is 12-48h, preferably 15-30h, and the electrolysis time can also be 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h and the like.
[0026] Preferably, as a further implementable solution, the AC voltage is controlled between 7-9V, and the voltage can also be 7.5V, 8V, 8.5V, 9.5V and so on.
[0027] The present invention provides a lithium ion battery negative electrode material prepared by the above preparation method, and the lithium ion battery negative electrode material has good application in equipment driving. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] By reading the detailed description of the preferred embodiment below, various other advantages and benefits will become clear to those of ordinary skill in the art. The accompanying drawings are only used for the purpose of illustrating the preferred embodiment and are not considered to be limitations of the present invention. In addition, the same reference symbols are used to represent the same components throughout the accompanying drawings.
[0029] Figure 1 The XRD pattern of the negative electrode material provided in Example 1 of the present invention;
[0030] Figure 2 TEM spectrum of the negative electrode material provided in Example 1 of the present invention;
[0031] Figure 3XRD spectrum of the negative electrode material provided in Comparative Example 1 of the present invention;
[0032] Figure 4 TEM spectrum of the negative electrode material provided in Comparative Example 1 of the present invention;
[0033] Figure 5 This is the SEM spectrum of the negative electrode material provided in Comparative Example 1 of the present invention;
[0034] Figure 6 This is the SEM spectrum of the negative electrode material provided in Comparative Example 2 of the present invention;
[0035] Figure 7 The XRD spectrum of the negative electrode material provided in Example 3 of the present invention;
[0036] Figure 8 This is a comparison chart of the cycle performance obtained in the experimental example of the present invention;
[0037] Fig. 9 This is a comparison chart of rate performance obtained in the experimental examples of the present invention. DETAILED DESCRIPTION
[0038] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0039] Example 1
[0040] A method for preparing a niobium-based lithium-ion battery negative electrode material comprises the following steps:
[0041] (1) A niobium wire and a carbon rod of appropriate length are used as the two ends of the electrode respectively, an 8 V alternating current is used as the power source, and a 1 mol / L NaCl solution is used as the electrolyte for electrolysis for 12 h until the reaction is completed, and a precipitate is obtained by suction filtration;
[0042] (2) drying the obtained precipitate in air, grinding it until there is no particle feeling, and then sintering it in air atmosphere at 500° C. for 12 h to obtain pure white powder (sodium niobate);
[0043] (3) The obtained sodium niobate is placed in a reaction kettle, and an excess of hydrochloric acid is added to carry out a hydrothermal reaction at 150° C. for 3 hours, followed by suction filtration and drying to obtain the prepared niobium-based lithium-ion battery negative electrode material.
[0044] Example 2
[0045] A method for preparing a niobium-based lithium-ion battery negative electrode material comprises the following steps:
[0046] (1) A niobium wire and a carbon rod of appropriate length are used as the two ends of the electrode respectively, and a 6V alternating current is used as the power source. A solution prepared by adding hydrochloric acid to a 0.5mol / L NaCl solution to adjust the pH to 4 is used as the electrolyte for electrolysis for 48 hours until the reaction is completed, and a precipitate is obtained by suction filtration;
[0047] (2) drying the obtained precipitate in air, grinding it until there is no particle feeling, and then sintering it in air atmosphere at 400° C. for 15 h to obtain pure white powder (sodium niobate);
[0048] (3) The obtained sodium niobate is placed in a reaction kettle, and an excess of hydrochloric acid is added to carry out a hydrothermal reaction at 100° C. for 12 hours, followed by suction filtration and drying to obtain the prepared niobium-based lithium-ion battery negative electrode material.
[0049] Example 3
[0050] A method for preparing a niobium-based lithium-ion battery negative electrode material comprises the following steps:
[0051] (1) A niobium wire and a carbon rod of appropriate length are used as the two ends of the electrode respectively, and electrolysis is performed for 30 hours with a 10V alternating current as the power source and a 1 mol / L NaCl solution as the electrolyte until the reaction is completed, and a precipitate is obtained by suction filtration;
[0052] (2) drying the obtained precipitate in air, grinding it until there is no particle feeling, and then sintering it in air atmosphere at 700° C. for 6 h to obtain pure white powder (sodium niobate);
[0053] (3) The obtained sodium niobate is placed in a reaction kettle, and an excess of NaOH is added to carry out a hydrothermal reaction at 200° C. for 6 hours, followed by suction filtration and drying to obtain the prepared niobium-based lithium-ion battery negative electrode material.
[0054] Comparative Example 1
[0055] A method for preparing a niobium-based lithium-ion battery negative electrode material comprises the following steps:
[0056] (1) A niobium wire and a carbon rod of appropriate length are respectively used as the two ends of the electrode, an 8 V alternating current is used as the power source, and a 1 mol / L NaCl solution is used as the electrolyte for electrolysis until the reaction is completed, and a precipitate is obtained by suction filtration;
[0057] (2) The obtained precipitate was dried in air and then ground until there was no particle feeling, and then sintered at 500° C. in air atmosphere for 12 h to obtain white powder (sodium niobate).
[0058] Comparative Example 2
[0059] A method for preparing a niobium-based lithium-ion battery negative electrode material comprises the following steps:
[0060] (1) A niobium wire and a carbon rod of appropriate length are used as the two ends of the electrode respectively, and 8 V AC is used as the power source and 1 mol / L NaCl solution is used as the electrolyte for electrolysis until the reaction is completed, and a precipitate is obtained by suction filtration;
[0061] (2) The obtained precipitate was dried in air and then ground until there was no particle feeling, and then sintered at 500° C. in air atmosphere for 4 h to obtain a light green powder (sodium niobate).
[0062] Comparative Example 3
[0063] A method for preparing a niobium-based lithium-ion battery negative electrode material comprises the following steps:
[0064] (1) A niobium wire and a carbon rod of appropriate length are respectively used as the two ends of the electrode, an 8 V alternating current is used as the power source, and a 1 mol / L NaCl solution is used as the electrolyte for electrolysis until the reaction is completed, and a precipitate is obtained by suction filtration;
[0065] (2) The obtained product was placed in a reactor, and an excess of hydrochloric acid was added to carry out a hydrothermal reaction at 200°C for 6 hours, followed by suction filtration to obtain an amorphous product.
[0066] (3) The obtained product was dried in air and then ground until there was no particle feeling, and then sintered at 500° C. in air atmosphere for 12 h to obtain white powder (niobium oxide).
[0067] Experimental Example 1
[0068] The materials prepared in Examples 1-3 and Comparative Examples 1-3 are negative electrodes, with 1 mol / L LiPF 6 in EC / DEC / DMC=1:1:1 as electrolyte, glass fiber as separator, assembled into 2025 button cell;
[0069] The battery performance was tested at 100mA / g, and the specific results are shown in the following table:
[0070] Table 1 Cycle comparison chart
[0071]
[0072] Table 2 Ratio comparison chart
[0073]
[0074] Depend on Figure 8It can be seen that the capacity of the battery at 1C is 148 mAh / g (compared to 145 mAh / g in Example 2, 119 mAh / g in Example 3, 112 mAh / g in Comparative Example 1, and 114 mAh / g in Comparative Example 2). After 100 cycles, the capacity is increased to 183 mAh / g (compared to 182 mAh / g in Example 2, 133 mAh / g in Example 3, 137 mAh / g in Comparative Example 1, and 131 mAh / g in Comparative Example 2), indicating a relatively high capacity increase.
[0075] Depend on Fig. 9 It can be seen that the capacity of the battery can reach 208 mAh / g at 0.1C (compared to 160 mAh / g in comparative example 1), the capacity is 158 mAh / g at 1C (compared to 122 mAh / g in comparative example 1), and the capacity is 105 mAh / g at 10C (compared to 70 mAh / g in comparative example 1), indicating that it has very good rate performance.
[0076] Since Comparative Example 3 was not prepared sequentially according to the scheme of the present invention, the substances obtained were different and there was no relevant test data.
[0077] In summary, the negative electrode material is initially prepared by using an alternating current electrolysis method, and then high-temperature sintering is performed to remove impurities therein and finally a hydrothermal reaction is performed to increase the interlayer spacing to obtain the prepared lithium ion battery negative electrode material; the present invention not only solves the problem of difficulty in preparing negative electrode materials for lithium ion batteries, but also increases the interlayer spacing of the material, thereby maintaining the cycle performance of the material, and improving the rate performance and specific capacity to meet the actual use requirements of lithium ion batteries.
[0078] Although the present invention has been illustrated and described with specific embodiments, it will be appreciated that many other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended to include all such changes and modifications within the scope of the present invention in the appended claims.
Claims
1. A method for preparing a negative electrode material for a lithium ion battery, characterized in that: The steps include: The niobium wire and the carbon rod are used as the two ends of the electrode, an inorganic solution is used as the electrolyte, the AC voltage is controlled between 6-10V, and electrolysis is filtered to obtain a precipitate, and the precipitate is subjected to high-temperature sintering and hydrothermal reaction to obtain a negative electrode material for a lithium-ion battery.
2. The preparation method according to claim 1, characterized in that: The inorganic solution includes at least one of sodium chloride, sodium hydroxide, hydrochloric acid and lithium chloride, preferably hydrochloric acid.
3. The preparation method according to claim 1, characterized in that: The high temperature sintering temperature is 400° C.-700° C., and the high temperature sintering time is 6-15 hours.
4. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 100-200° C., and the time of the hydrothermal reaction is 3-12 hours.
5. The preparation method according to claim 1, characterized in that: The acid used in the hydrothermal reaction includes at least one of acetic acid, succinic acid, oxalic acid, malonic acid, hydrochloric acid, formic acid, propionic acid and oxalic acid, preferably hydrochloric acid.
6. The preparation method according to claim 1, characterized in that: The electrolysis time is 12-48 hours, preferably 15-30 hours.
7. The preparation method according to claim 1, characterized in that: The AC voltage is controlled between 7-9v.
8. A lithium-ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the negative electrode material for a lithium-ion battery prepared by the preparation method according to any one of claims 1 to 7 and the negative electrode material for a lithium-ion battery according to claim 8 in device driving.